Pengaruh Penerapan Manajemen Risiko terhadap Tingkat Profitabilitas di Perbankan: Studi Empiris pada Perusahaan Perbankan yang Terdaftar pada Bursa Efek Indonesia Periode 2013 – 2017 - Satria Berbudi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research examines the effect of risk management (NPL, LDR, BOPO, CAR, NIM) on profitability in banks (ROA & ROE) listed on the Indonesia Stock Exchange for the 2013-2017 period. This research uses a descriptive-verification method, with samples taken in this research of 20 banking companies listed on the Indonesia Stock Exchange. The analysis used in this research uses multiple regression analysis of panel data. Classical assumption tests used in this research include normality, multicollinearity, heteroscedasticity and autocorrelation tests. The partial research results show that credit risk has an effect on profitability (ROA & ROE). Liquidity risk has no effect on profitability (ROA & ROE). Operational risk affects profitability (ROA & ROE). Risk capital has no effect on ROA profitability and has an effect on ROE profitability. Market risk affects profitability (ROA & ROE). Simultaneously credit risk, liquidity risk, operational risk, capital risk and market risk influence banking profitability (ROA) with an Adjusted R2 value of 92.77%, the remaining 7.23% is caused by other variables outside the variables mentioned. involved in this research. Meanwhile, ROE, simultaneously credit risk, liquidity risk, operational risk, capital risk and market risk influence banking profitability (ROE) with an Adjusted R2 value of 91.23%, the remaining 8.77%.